Environment-based Learning as a Learning Source for Childhood Education Program (Universitas Negeri Semarang, 2019)
Learning environment can influence the development of the academic and psychological abilities of every human being in his life, including children. This study aims to analyze environmental-based learning as a source of learning for children. The research is qualitative research, and it was carried out at the Cerdas Chilhood Education Program in Sukorejo-Kendal. The subjects of the study were the teacher of Cerdas Chilhood Education Program in Sukorejo-Kendal. Data analysis was done using an interactive model. The results of the study showed that the planning of learning in utilizing the environment of RPS (Semester Program), RPPM (Weekly Program), and RPPH (Daily Program). The implementation of learning in using the environment as a learning resource includes the implementation of opening activities, main activities and closing activities. Assessment of learning in utilizing the environment as a learning resource includes checklists, anecdotal notes, and artworks. The environment used as a learning resource starts from planning, implementation, and assessment including three types of environments, namely the natural environment, social environment, and artificial environment. The obstacles in applying environment-based learning as a source of learning are climates and location of Sukorejo village in a mountainous area that have fairly high rainfall intensity so that sometimes the plans that have been made cannot be implemented and assessed. The participation of parents, teachers, students, and the community is needed to carry out maximum environment-based learning.